Prevalence and associated factors of neonatal hypothermia among newborn within six hours of birth in Pokhara academy of health sciences, pokhara. - Adhikari,Rita (2020)
ABSTRACT: Background: Hypothermia is one of the important causes of neonatal morbidity and mortality. Every 1oC decrement of body temperature increases mortality by 80 %. Persistent hypothermia leads to cold injury and cold injury results edema, scleroderma, pulmonary hemorrhage, jaundice, and death. Objective: To identify the prevalence and associated factors of neonatal hypothermia among newborns within six hours of Birth in Pokhara Academy of Health Sciences. Methods: Ethical approval was taken from Nepal Health Research Council (Ref. 2881) and Pokhara Academy of Health Sciences (Ref. 5.2077/078). The quantitative descriptive cross sectional study design was used. Data was collected from 402 systematic randomly selected respondents from August 1 to September 30, 2020 by using structured format and Digital thermometer MT 100. Data was cleaned and entered in SPSS version 20. Bivariate logistic regression was used to determine the candidate variables (p<0.25) for multivariate logistic regression analysis. Adjusted Odds ratio (AOR) with 95% CI was used as a measure of association. The p value less than 0.05 in the multivariate logistic regression was considered as statistical significance. Results: The prevalence of Neonatal hypothermia within six hours of birth in the study area was about 43 percent. The significant independent factors of neonatal hypothermia were maternal age after 35 years (p=0.03, AOR: 4.087, 95% CI: 1.12-14.97), inadequate antenatal clinic visit (p=0.03, AOR: 0.52, 95% CI: 0.29-0.94), low birth weight babies (p=0.00, AOR: 0.433, 95% CI: 0.24- 0.77) and who had resuscitated at birth (p =0.00, AOR: 3.808)95% CI: 1.69- 4.65). Conclusion: The prevalence of Neonatal hypothermia in the study area was high. Mothers age more than 35 years, inadequate antenatal clinic visit, low birth weight and resuscitation at birth were independent factors of Neonatal hypothermia. Therefore, special attention is needed for the thermal care of low birth weight neonates and warm resuscitation.